Efektivitas Pemberian Konsentrasi Pupuk Daun Growmore (32-10-10) dan Jenis Media Tanam Terhadap Pertumbuhan Tanaman Anggrek Dendrobium Airey Peach x Dendrobium discolor - Vallepy, Andini; Yeni, Yeni; Ali, Fahri; Erfa, Lisa (Journal of Horticulture Production Technology, 2024)
Orchids are the largest type of flower in the Orchidaceae family of ornamental plants, and this ornamental plant has high economic value. The problem in cultivating orchids is that orchid plants tend to grow slowly. The aim of this research was to determine the most effective concentration of Growmore leaf fertilizer (32-10-10); the best type of planting medium for orchid growth; and to find out the best combination of Growmore foliar fertilizer (32-10-10) with the type of planting medium. This research was carried out using a factorial randomized block design (RBD) with 2 factors and repeated 3 times. The first factor is concentration of Growmore leaf fertilizer (32-10-10) with concentrations of 1 g.l-1 (P1), 2 g.l-1 (P2), 3 g.l-1 (P3), and 4 g.l-1 (P4). The second factor is the type of planting medium consisting of a mixture of wood charcoal and cocopeat (M1), ferns with wood charcoal (M2), and ferns with cocopeat (M3). The results of study showed that the effectiveness of giving Growmore leaf fertilizer (32-10-10) at concentrations of 2 g.l-1, 3 g.l-1, and 4 g.l-1 it showed better results on the observed variables of plant height, increase in number of leaves, and longest leaf length compared to 1 g.l-1.  The use of fern + wood charcoal planting media showed better results in the longest root length observation variable. There is no best combination between Growmore foliar fertilizer (32-10-10) and the type of planting media for the growth of Dendrobium Airey Peach x Dendrobium discolor orchids.